Segmentation and 3D reconstruction of microbial biofilms - Bouchet, Agustina (2013)
Capability of microbial biofilms to form biofilms is really important in biotechnology industries, environmental applications and medical applications. Therefore, the study of the structure and development of these organisms is essential. In this paper we develop and implement an algorithm, based on Mathematical Morphology, to analyze the structure and growing of microbial biofilms. This algorithm allows segmentation of a stack of images acquired from in vivo observation of microorganisms, using an inverted phase contrast microscope. Finally, a 3D reconstruction for an efficient visualization of the structure and topography of biofilms is done.